Arctic and subarctic gateways for private nautical tourism : a feasibility study for marina development in Ísafjörður, Iceland - Brötzmann, Maik, 1979- (2013)
Verkefnið er lokað til 31.8.2014. Private nautical tourism in arctic and subarctic settings has been generally neglected in polar tourism studies. This thesis draws attention towards private nautical tourism as a viable economic supplement and alternative form of tourism for rural coastal communities. Understanding this opportunity, its economic and management implications, and its users’ characteristics are the core of this research. The study covers basic concepts and provides a feasibility assessment for marina development via SWOT analysis for a gateway functioning community in the secluded Westfjords of Iceland. Research data are compiled from secondary sources, interviews, questionnaires and a synthesis of related scientific articles, industry and policy documents, media publications, and baseline information. The case study confirms the conditional economic feasibility of private nautical tourism developments in high-latitude gateway locations and reveals users as adventure-seeking, authenticity-driven and environmentally-motivated. It is concluded that marina-oriented developments meeting certain conditions can be beneficial to remote rural arctic and subarctic communities in diverse ways. However, because of short and unpredictable seasons and changing user volumes, private sector marinas must be integrated with other business in the community to be profitable. Ferðaþjónusta við einstaklinga sem sækja í siglingar á norðlægum breiddargráðum hefur fengið litla athygli í fræðilegri umræðu um ferðmennsku á norðurslóðum. Í þessari ritgerð er spjótunum því beint að þessari gerð ferðamennsku sem mögulegu arðbæru atvinnutækifæri fyrir smærri strandbyggðir. Í því tilliti er mikilvægt að efla skilning á eiginleikum og hagrænum ávinningi þessarar ferðmennsku sem og þeim þáttum sem skipta máli varðandi hegðun og neyslu ferðamannanna. Markmiðið er því að gera viðeigandi grunnhugtökum skil og byggir rannsóknin á hagkvæmnisgreiningu - SWOT greiningu - fyrir hinar strjálu hafnarbyggðir Vestfjarða, en greiningin ...